Analisis Perancangan Sistem Pakar Pola Latihan Untuk Mencapai Body Goals Menggunakan UML - Setiana, Elia; Budiman, Budiman; Rakhman A, R. Yadi; Ramadhan, M. Rizki (Masoem University, 2023)
Technological developments and awareness of the importance of health and physical fitness have encouraged people to look for effective solutions in achieving their desired body goals. Expert systems are one potential approach to assist individuals in designing exercise patterns that suit their goals. This system development method uses UML as a tool for analyzing and designing expert system structures. This expert system will utilize expert knowledge in the fields of fitness and nutrition to provide personalized and effective recommendations. Additionally, integration with technology will allow users to monitor their progress in real-time and receive recommendation updates according to their individual progress.The results of this research are architectural designs consisting of Usecase Diagrams, Activity Diagrams, Class Diagrams, Sequence Diagrams, Deployment Diagrams which can then be used as a reference for creating this expert system application system so that it is hoped that the complete system can become a useful tool and can make a contribution. positive in helping users achieve their body goals with a more focused and effective approach.